2019
DOI: 10.3390/min9050268
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analytical Approach to Define the Compositional and Textural Features of Mortars Used in the Underwater Archaeological Site of Castrum Novum (Santa Marinella, Rome, Italy)

Abstract: This paper aims to carry out an archaeometric characterization of mortar samples taken from an underwater environment. The fishpond of the archaeological site of Castrum Novum (Santa Marinella, Rome, Italy) was chosen as a pilot site for experimentation. The masonry structures reached the maximum thickness at the apex of the fishpond (4.70 m) and consisted of a concrete conglomerate composed of slightly rough stones of medium size bound with non-hydraulic mortar. After sampling, for a complete characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Starting from the in-depth knowledge of the pilot sites, the methodological approach (Figure 1) planned within the project will lead to the improvement of the already existing management practices for UCH sites, giving as main results innovative tools and materials for promoting conservation strategies of underwater sites [25][26][27], as well as their knowledge, promotion, and fruition in a sustainable way. This approach will be driven by several steps which can be summarized as follows: (a) the realization of a network of knowledge and exchanges of skills through training activities; (b) the analysis and study of the three pilot sites (from historical/archaeological, environmental, geological, biological, etc.…”
Section: Methodological Approach and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the in-depth knowledge of the pilot sites, the methodological approach (Figure 1) planned within the project will lead to the improvement of the already existing management practices for UCH sites, giving as main results innovative tools and materials for promoting conservation strategies of underwater sites [25][26][27], as well as their knowledge, promotion, and fruition in a sustainable way. This approach will be driven by several steps which can be summarized as follows: (a) the realization of a network of knowledge and exchanges of skills through training activities; (b) the analysis and study of the three pilot sites (from historical/archaeological, environmental, geological, biological, etc.…”
Section: Methodological Approach and Objectivesmentioning
confidence: 99%
“…In the framework of the TECTONIC project, a transversal customizable modular tool for the management of UCH will be developed, suitable to be applied in the submerged environment and addressing a wide range of appropriate solutions [5,8,9,14,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] that are still missing or are very scarce in the market of cultural and sustainable tourism. Up to now, the research addressed the different sectors separately.…”
Section: Final Remarksmentioning
confidence: 99%
“…Particularly, the visitor experience outside of the "wet" environment is showing significant advantages, especially in presenting underwater sites that are inaccessible to the large public (i.e., people who do not like diving or are unable to do it). So, the virtual tools in the KACs are not limited to entertain users but have a pedagogical value, by providing additional information about the historical, biological, archaeological context [1][2][3]6,7,[30][31][32][33][34][35][36][37][38].…”
Section: The Model Of the Knowledge Awareness Centrementioning
confidence: 99%
“…At that time, it was found that this type of materials has many beneficial characteristics, such as: increased strength after a long period of curing, increased corrosion resistance, high resistance to impact and dynamic loads, increased resistance to high temperatures, and increased electrical resistivity, e.g., [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The numerous advantages of using LCFA as concrete additives are presented, i.e., in [ 39 , 40 , 41 ]. According to the data contained therein the incorporation of LCFA: improve the workability of concrete mixture, increases the water requirement, setting time and soundness of cement paste specimens and decrease the drying shrinkage of hardened cement paste.…”
Section: Introductionmentioning
confidence: 99%